Voices of Chinese private college EFL students: unveiling preferences in written corrective feedback - Mudan Cai; Joseph Ramanair (International Journal of Evaluation and Research in Education (IJERE), 2026)
Despite the growing body of research on the impact of written corrective feedback (WCF) on intermediate and upper-level students in Chinese public universities, limited attention has been paid to the preferences of lower- and intermediate-level English as a foreign language (EFL) students in Chinese private colleges regarding various types of WCF. To address this gap, the current study examined students’ experiences with and preferences for WCF. A quantitative survey design was adopted, with data collected from 30 EFL students at a private college in Mainland China using an online self-administered questionnaire. The results showed: i) students’ preferences for WCF types were consistent with their feedback experiences; ii) students most commonly received direct feedback focused on content, while spelling gained the least feedback; and iii) students most preferred direct feedback on content and grammar, while indirect feedback on organization and spelling was least favored. The findings suggest that WCF remains valuable for EFL learners and their English as a second language (ESL) counterparts. It is recommended that EFL writing teachers in similar contexts tailor their feedback practices by prioritizing students’ preferences, particularly by emphasizing direct feedback on content and grammar, to boost engagement and learning outcomes.